Development of Shelf-Stable Brined Vegetables by Lactic Acid Fermentation - Suresh, E R (Journal of Horticultural Sciences, 2008)
Preservation of vegetables, viz., bitter gourd, carrot, capsicum, cucumber, French bean and gherkin by lactic acid fermentation was attempted. Properly prepared vegetables, packed in brine containing 2.5% equilibrated salt with additives, were allowed to undergo fermentation by their natural flora and this was compared with pure culture fermentation by Lactobacillus plantarum. Fermented vegetables had 0.5 to 1.31% lactic acid, with pH values ranging from 2.97 to 4.02, at the end of 4 weeks of fermentation at 20 ± 2°C. In general, fermentation by L. plantarum resulted in a slightly faster rate of acid production compared to that by natural flora. Mustard powder at 1% concentration was found to be useful as alternate preservative in vegetable fermentation. Fermented vegetables had acceptable quality in terms of colour, texture, flavour, taste and were microbiologically stable for six months of storage at room temperature (25 ± 8°C).
Keywords: Vegetables; Lactic Acid Fermentation; Natural Flora; Lactobacillus plantarum